Psychological Perspectives on Yoga and Meditation in India (International Journal of Food and Nutritional Sciences, 2022)
Yoga and meditation, deeply embedded in India’s spiritual, cultural, and physical traditions, have evolved over centuries to become global practices, now widely recognized for their psychological benefits. Originally developed for spiritual growth, these practices have been increasingly studied for their impact on mental health, emotional regulation, and cognitive processes. This paper explores the psychological perspectives of yoga and meditation within the Indian context, examining their therapeutic effects on mental well-being. It begins by tracing the historical origins of these practices in ancient Indian traditions, including the Vedic and Upanishadic texts.